The limits of polymorphism in Liolaemus rothi: Molecular and phenotypic evidence for a new species of the Liolaemus boulengeri clade (Iguanidae, Liolaemini) from boreal Patagonia of Chile - Pincheira-Donoso, Daniel; Scolaro, J. Alejandro; Schulte Ii, James A. (Zootaxa, 2007)
Studies conducted over the last few years in Andean boreal Patagonia along the border of Argentina and Chile (36°50’S–37°53’S) have shown that its reptile diversity is comprised of several endemic lizards. Increasing research has led to recognize a number of cryptic iguanian species from previously named taxa. In this area is common the only known Chilean population of the Patagonian Liolaemus rothi, considered as a polymorphic species with wide geographical distribution. In this paper, we provide evidence to support the hypothesis that such population represents a new taxon, herein described as Liolaemus hermannunezi. This new species occurs in the southeastern areas of Laguna del Laja, in the Los Barros and Río de Los Pinos basins of Antuco Volcano (1428–1521 m) in the Bio Bio Region. Liolaemus hermannunezi is closely related to L. rothi, from which is significantly differentiated by molecular variables. In addition, this new species appears to be related to L. loboi and L. sagei, from which differs in having a smaller body size, a distinctive colour pattern and an isolated geographical distribution. Liolaemus hermannunezi is known from the boreal Patagonia of Chile, whereas L. loboi, L. rothi, and L. sagei are endemic to Argentinean Patagonia. The new species is a member of the boulengeri clade, diagnosed by the presence of a patch of abruptly enlarged scales on the posterior medial surface of the thigh, a character that is more conspicuous in adult males. Finally, a phylogenetic hypothesis for 67 Liolaemini taxa based on DNA sequences is presented